Identity from Symbolic Networks: The Rise of New Hollywood - Katharina Burgdorf; Henning Hillmann (Sociological Science, 2024)
To what extent may individual autonomy persist under the constraints of group identity? This dualism is particularly salient in new movements that value individual creativity above all, and yet have to muster community cohesion to establish a new style. Using the case of New Hollywood in the 1960s and 1970s, the authors show how this movement reconciled the demands of collective identity and collaboration in film production with their commitment to the individual filmmaker's artistic autonomy. Using information from the Internet Movie Database on 17,425 filmmakers who were active between 1930 and 1999, the authors show that a cohesive symbolic network, in which New Hollywood filmmakers shared references to a canon of revered films, served as a foundation for the collective identity of this new artistic movement. References include allusions to iconic scenes, settings, and shots of classic films. In contrast, collaborations in film projects yielded a fragmented network that did little to support the creative enterprise of New Hollywood. The evidence suggests that symbolic ties through shared citations allowed New Hollywood filmmakers to realize their vision of autonomous auteur filmmaking and to draw symbolic boundaries that separated them from the old Hollywood studio system.